The attitudes and views of Firat and Uludag University Faculty of Veterinary Medicine students on the subject of dog psychology - Dogan, Ozlem; Ozkul, Turel; Ozen, Abdullah (Ankara Univ Press, 2011)
The aim of this study was to determine the attitudes and views of Firat and Uludag University Faculty of Veterinary Medicine students on the subject of dog psychology. For this purpose a survey was applied to 401 students. Statistycal analysis showed that a positive attitude was observed (4>) concerning the care level of dog psychology by 97.3% of participants. Significant differences (p<0.001) were determined among the attitudes of participants on the variables of gender, pet ownership and having a dog as a pet. Among the participants who accepted that dogs have some cognitive features like curiosity, intelligence, reasoning ability and discernment, the proportion of Uludag University students was determined to be higher than that of the Firat University students (p<0.001). Similarly, among the participants who thought that biological and environmental factors like clipping (p<0.01), genetical properties (p<0.01) and seasonal conditions (p<0.05) are effective on the psychology of dogs, the proportion of Uludag University students was determined to be higher than that of the Firat University students. Significant relation was determined between the knowledge level of students related to dogs and the care level of dog psychology.
Fırat ve uluda? üniversitesi veteriner fakültesi ö?rencilerinin kopek psikolojisi konusundaki tutum ve görüşleri
Keywords: Dog psychology; attitude; students of veterinary faculty; veterinarian